KEMANDIRIAN ANAK USIA 5-6 TAHUN DALAM KELUARGA ORANG TUA TUNGGAL (STUDI KASUS DI CIPINANG BESAR SELATAN, JATINEGARA, JAKARTA TIMUR) - Anggieta Suci Wardani; Sri Wulan; Hapidin Hapidin (STIT Al-Marhalah Al-Ulya Bekasi, 2021)
AbstrackThe purpose of this research is to determine and describe the independence of children aged 5-6 years who live with single parents in the presence of father only. This research uses qualitative research methods with the type of case study research. This research was conducted at the residence of a single parent family located in Cipinang Besar Selatan RT002 / RW05 No.39, Jatinegara, East Jakarta. Data collected by observation, interview and documentation. Data analysis uses Campbell's pattern matching model which includes general of statement, sorting the statement and development of the concept map. The results showed that the independence contained in the research subjects were : 1) the ability to help himself in daily life, 2) initiative in doing various things or activities, 3) responsible for what was done and 4) the ability to adapt the environment. This independence is inseparable from the opportunities given by parents to children so that children can do their own activities. The results of this study indicate that children's independence can be built and developed by single parents by providing opportunities to children such as, teaching independence directly to children, habituation, and give advice and direction their daily activities and choosing not to use ART services in caring for children.Â Keywords : Independence, Child Ages 5-6 Years, Family Single Parents